How to prove the existence of God: an argument for conjoined panentheism - Burns, Elizabeth (International journal for philosophy of religion, 2019)
This article offers an argument for a form of panentheism in which the divine is conceived as both 'God the World' and 'God the Good'. 'God the World' captures the notion that the totality of everything which exists is 'in' God, while acknowledging that, given evil and suffering, not everything is 'of' God. 'God the Good' encompasses the idea that God is also the universal concept of Goodness, akin to Plato's Form of the Good as developed by Iris Murdoch, which is inextricably conjoined with God the World because it is the nature of the world which determines the nature of perfect Goodness. This form of 'conjoined' panentheism yields a concept of divine personhood which includes both divine agency and human/divine engagement. God the Good is an agent of change by providing human persons with a standard of Goodness against which to measure the goodness of their own actions, while God the World provides the physical embodiment through which God acts. Human engagement with the divine may take a number of forms and may lead to moral action, the means by which the divine acts upon the world and changes it for the better.